ACADEMICIAN D. N. ANUCHIN AND HIS «REPORT ON A TRIP TO DAGESTAN IN THE SUMMER OF 1882» - Magomedov, Amirbek Dz. (History, Archeology and Ethnography of the Caucasus, 2024)
The article is dedicated to the outstanding Russian geographer, ethnographer, academician D.N. Anuchin (1843–1923). 2023 marks the 180th anniversary of his birth. In 1896 he was elected academician of the Imperial St. Petersburg Academy of Sciences. The merits of D.N. Anuchin in the field of domestic geography were noted back in 1948 in a special decree of the Soviet government to perpetuate his memory. In this document, D.N. Anuchin was called “the largest Russian geographer, the creator of the Russian university geographical school”. D.N. Anuchin founded the Department of Geography at Moscow University, which laid the foundation for its modern Faculty of Geography. Well known is D.N. Anuchin and Dagestan scientists as an archaeologist (participation in exploration) and ethnographer, who left a legacy of interesting materials about Dagestan. His “Report on a trip to Dagestan in the summer of 1882, made with the assistance of the Imperial Russian Geographical Society” (1884) was actively studied by Dagestan archaeologists and ethnographers. Assessments of D.N. Anuchin’s observations are given in the works of Corr. Member of the RAS R.M. Munchaev, academic Kh.A. Amirkhanov, and other researchers. At the same time, in the Internet space and in scientific publications, the merits of D.N. Anuchin have not been fully studied. Popular scientific and biographical information about the scientist is presented in more detail. The Yandex search engine gives 12 thousand responses to the name “D.N. Anuchin" Among the publications, the most famous is the book about D.N. Anuchin by G.V. Karpov, published back in 1954. The merits of D.N. have not been sufficiently studied. Anuchin on the “Dagestan” topic. While in Dagestan in 1882, he conducted an archaeological exploration of a significant part of its territory to identify Stone Age monuments, and collected valuable material on folklore, ethnography and traditional crafts of the peoples of Dagestan.
Keywords: D. N. Anuchin; Russian archaeological societies; ethnography; folklore of Dagestan; folk crafts p. Kubachi